MODEL OF AIRCRAFT ELECTRICAL POWER SUPPLY SYSTEM CHANNEL OF ALTERNATIVE CURRENT RUNNING ON A GENERALIZED UNBALANCED THREE-PHASE LOAD - A. G. Demchenko (Научный вестник МГТУ ГА, 2017)
This article is devoted to mathematical modeling of the channel of AC on-board power supply systems (PSS) when running on static active-inductive load, connected on a "wye with neutral" and "delta". The mathematical model of aircraft synchronous generator, electricity distribution, three-phase static active-inductive load are considered. When making a mathematical description the author used the equations for the voltages of windings and flux linkages circuits of the stator and rotor of the generator in a stationary system phase coordinates "ABC". When considering the mathematical model of the distribution system, the equations that took into account the drop of the voltages on the active and inductive resistance of the distribution system power wires were used. When considering the mathematical models of three-phase static loads connected on a "wye with neutral" and "delta", the equations that took into account the drop of the voltages on the active and inductive resistance loads were used. The matrix equations system of channel PSS AC when running on a generalized three-phase static active-inductive load was obtained. The three phase static loads scheme connected according to the "delta" scheme was converted to "wye" to simplify the solution of channel PSS AC circuit matrix equations system. The choice of the phase coordinates system "ABC" for the mathematical description of the generator, distribution system and the static load was made due to its advantage over the coordinate system "dq", because the equation written in phase coordinates are valid for symmetric and asymmetric modes of the generator, while the equations written in the coordinate system "dq" will be valid only for symmetric modes. As a result of joint solution of the generator equations, distribution system, three-phase static loads there were obtained the formulae for the generator stator winding phases, generator phases currents, the voltage drops on the load phases and load phases currents connected on a "wye with neutral" and "delta".